1999
DOI: 10.1016/s0735-1097(99)00444-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing primary angioplasty with a strategy of short-acting thrombolysis and immediate planned rescue angioplasty in acute myocardial infarction: the PACT trial

Abstract: Tailored thrombolytic regimens compatible with subsequent interventions lead to more frequent early recanalization (before cath arrival), which facilitates greater LV function preservation with no augmentation of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
2
19

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(132 citation statements)
references
References 34 publications
4
107
2
19
Order By: Relevance
“…Patients in cardiogenic shock were excluded or poorly represented in most trials. The fibrinolytic agent used was streptokinase in two trials (8,9), alteplase (rt-PA) in two trials (10,11) and tenecteplase (TNK) in three trials (12)(13)(14). In the ASSENT-4 and WEST studies (study acronyms are spelled out in Appendix 1), 20% and 40% of patients were enrolled in the prehospital setting, respectively.…”
Section: Pci Facilitated By Fibrinolytic Therapy Alonementioning
confidence: 99%
See 1 more Smart Citation
“…Patients in cardiogenic shock were excluded or poorly represented in most trials. The fibrinolytic agent used was streptokinase in two trials (8,9), alteplase (rt-PA) in two trials (10,11) and tenecteplase (TNK) in three trials (12)(13)(14). In the ASSENT-4 and WEST studies (study acronyms are spelled out in Appendix 1), 20% and 40% of patients were enrolled in the prehospital setting, respectively.…”
Section: Pci Facilitated By Fibrinolytic Therapy Alonementioning
confidence: 99%
“…The risk of reinfarction was 2.0% to 7.0% with facilitated PCI and 1.0% to 3.7% with nonfacilitated PCI. In addition, facilitated PCI had no effect on the following surrogate end points: ST segment resolution at 60 min (GRACIA-2 [12], ADVANCE MI [15]), infarct size (GRACIA-2, BRAVE [16]), convalescent LVEF (SANI [8], PACT [10], PRAGUE-1 [17], GRACIA-2, BRAVE [16]), exercise stress test performance (PACT [10]) or MACE up to one year of follow-up (LIMI [11], PACT [10], PRAGUE-1 [18]). …”
Section: Pci Facilitated By Fibrinolytic Therapy Alonementioning
confidence: 99%
“…This strategy is therefore very different from thrombolysis per se and probably explains why the results achieved by prehospital thrombolysis in CAPTIM are very different from studies reported in the meta-analysis of prehospital versus hospital thrombolysis. 4 Some studies have suggested that combining early thrombolysis with subsequent PCI in the setting of STEMI may be a very effective strategy, [22][23][24] particularly because it would reduce the time to optimal myocardial reperfusion 25 compared with primary PCI and may reduce the risk of recurrent infarction compared with in-hospital thrombolysis. This may be especially true of a strategy of prehospital thrombolysis, subsequent angiography, and, if needed, percutaneous intervention, which in a previous matched case-control study appeared to achieve in-hospital outcomes similar to those of primary angioplasty.…”
Section: Steg Et Al Prehospital Rtpa Vs Primary Pcimentioning
confidence: 99%
“…Early, spontaneous reperfusion occurs in a small but significant proportion of IRAs (4,5), and the majority are reperfused with thrombolytic therapy. It is difficult to determine whether patency has been achieved at a given time in most patients without cardiac catheterization.…”
mentioning
confidence: 99%